2022
DOI: 10.1101/2022.02.16.480507
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HIV-1 preintegration complex preferentially integrates the viral DNA into nucleosomes containing trimethylated histone 3-lysine 36 modification

Abstract: HIV-1 DNA integration into the host chromosomes is carried out by the preintegration complex (PIC). The PIC contains the viral DNA, virally encoded integrase enzyme and other critical viral/host factors. The PIC-associated viral DNA is preferentially integrated into gene bodies of actively transcribing genes. Here, we identify a biochemical mechanism underlying the preference of PIC-mediated viral DNA integration (PIC-VDI). Specifically, we observed that the PIC-VDI into human chromatin is preferred over the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 142 publications
(282 reference statements)
0
1
0
Order By: Relevance
“…Significantly, HIV integrase interacts with the PWWP domain containing protein LEDGF, a reader of the H3K36me3 mark, raising the possibility that H3K36me3 could potentially contribute to HIV integration [32]. Indeed, in vitro integration assays demonstrate that H3K36me3 modified histones significantly enhance integration of HIV preintegration complexes (PICs) into nucleosomal substrates [33,34]. Interestingly, it has also recently been shown that the chromatin insulator CTCF also can mediate HIV integration in microglia and is enriched near regions of high H3K36me3 [35].…”
Section: Introductionmentioning
confidence: 99%
“…Significantly, HIV integrase interacts with the PWWP domain containing protein LEDGF, a reader of the H3K36me3 mark, raising the possibility that H3K36me3 could potentially contribute to HIV integration [32]. Indeed, in vitro integration assays demonstrate that H3K36me3 modified histones significantly enhance integration of HIV preintegration complexes (PICs) into nucleosomal substrates [33,34]. Interestingly, it has also recently been shown that the chromatin insulator CTCF also can mediate HIV integration in microglia and is enriched near regions of high H3K36me3 [35].…”
Section: Introductionmentioning
confidence: 99%